(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Rajavrat known as Lapis lazuli stone is one of the semiprecious stone in Indian alchemy placed under Upratna Varg. Lapis lazuli stone is made up of Metamorphic Rock and chemically it is mixture of minerals (Na S3-Al) Al2 (SiO4)3 with lazurite. It is royal blue in colour and used since century for ornaments, beads and making of decorative items. The ‘blue pigment’ known as ultramarine is extracted from it and used in paintings and colouring agent since middle age. It is one of the most spiritually used stone worldwide and used therapeutically in different system of medicines. In Ayurveda it is mentioned in most of the Rasagranthas and therapeutically given in various ailments mainly in diabetes, alcoholism, and urinary disorders. Its identification, different purification methods, therapeutic uses are described in various texts. An attempt has been made to compile and provide information regarding its historical presence, mineralogical identification, physico-chemical properties and therapeutic uses in different system of medicine.